2018
DOI: 10.1093/scan/nsy062
|View full text |Cite
|
Sign up to set email alerts
|

Child brain exhibits a multi-rhythmic response to attachment cues

Abstract: Research on the human parental brain implicated brain networks involved in simulation, mentalization and emotion processing and indicated that stimuli of own parent–child interaction elicit greater integration among networks supporting attachment. Here, we examined children’s neural activation while viewing own parent–child interactions and asked whether similar networks activate when children are exposed to attachment stimuli. Sixty-five 11-year-old children underwent magnetoencephalography (MEG) while observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 72 publications
(140 reference statements)
0
34
0
Order By: Relevance
“…We found that parental brain activations in infancy predicted the child's emotion regulation, stress management, and symptom formation across the first seven years of life 109‐111 . In parallel, sensitive and synchronous parenting longitudinally shaped the child's affiliative brain in adolescence 112,113 . Finally, humans' large associative cortex enables humans to find meaning through love to abstract ideas, such as homeland or God, and extend affiliations to fellow‐humans, pets, or the Earth's flora and fauna, all supported by the same network 85 .…”
Section: Core Components Of the Neurobiology Of Affiliationmentioning
confidence: 89%
See 1 more Smart Citation
“…We found that parental brain activations in infancy predicted the child's emotion regulation, stress management, and symptom formation across the first seven years of life 109‐111 . In parallel, sensitive and synchronous parenting longitudinally shaped the child's affiliative brain in adolescence 112,113 . Finally, humans' large associative cortex enables humans to find meaning through love to abstract ideas, such as homeland or God, and extend affiliations to fellow‐humans, pets, or the Earth's flora and fauna, all supported by the same network 85 .…”
Section: Core Components Of the Neurobiology Of Affiliationmentioning
confidence: 89%
“…Neural oscillations play an important role in predictive coding: alpha oscillations participate in building predictions, beta oscillations in assessing the accuracy of these predictions, and gamma oscillations in prediction error, the constant pitting of the brain's predictions with incoming information 196,197 . Synchronous experiences provide a template for polyrhythmic coherence that enables multisensory representation of the body in the world 197 and involves the integration of alpha, beta and gamma rhythms in formation of social predictions during real‐life events 112 .…”
Section: Synchrony From Infancy To Adulthood: the Unfolding Of Resilimentioning
confidence: 99%
“…In parallel, the infant's emerging awareness of own body and construction of primitive representations of self are initiated by maternal-infant interactions (Atzil et al, 2018;Fotopoulou and Tsakiris, 2017). Indeed, interoceptive activations in the parental brain shaped children's later social competencies and insular activation in the child's brain to attachment cues (Pratt et al, 2019(Pratt et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The system shows construct and predictive validity, test-retest reliability, and sensitivity to cultural contexts, interacting partner, and multiple psychopathological conditions [for a review see 50 ]. Consistent with prior research, we used the parent-child synchrony CIB construct; 46,47,[51][52][53] , computed by averaging several CIB codes.…”
Section: Behavior Codingmentioning
confidence: 99%